Dividend Persistence and Firm Value of Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) - Lanaya Husnul Safriana; Elin Erlina Sasanti (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2024)
Investors need information to help make the proper investment decisions. One of this information is regarding the dividend policy implemented by the company. This research aims to determine the influence of dividend persistence on company value. Research was conducted on manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2017-2022 period. The sampling technique used was purposive sampling with a total sample size of 152 companies. Data was obtained from the annual report published on the BEI website www.idx.co.id. The statistical method used to test the research hypothesis is multiple linear regression. The results of data analysis show that dividend persistence affect company value. The results of this research confirms Signalling Theory as well as the results of previous research of the importance of dividend persistence in providing signals to investors regarding the condition and prospects of the company.